Hydroclimatic assessment of water resources of low Pacific islands: evaluating sensitivity to climatic change and variability. (10th June 2013) - de Freitas, C. R.; Helbig, M.; Matzarakis, A.
Abstract For many of the low islands of the tropical Pacific, freshwater is a scarce resource. Water catchment areas are small and groundwater storage is a shallow fresh water lens. The high hydraulic conductivities of the coral and sand substrate means surface water is limited. Realization of the possible impact of climate change has highlighted the sensitivity of island communities to the availability of water. However, impact evaluation requires specialized data as well as appropriate sensitivity assessment methodologies. This is the second of a two part study. The first addressed the data problem by assembling and validating a suitable database. The second develops an island water balance model and applies a sensitivity assessment. Data are at a 2.5° × 2.5° latitude–longitude grid resolution for the Pacific bounded by coordinates 30°S to 30°N and 155°E to 120°W. Output is in the form of Climate Change Sensitivity Index maps that show the impact on the spatial redistribution of climate‐determined freshwater resources under various climate scenarios. The method allows for estimation of water deficits or surpluses for low islands located in any part of the study area. Areas of high sensitivity to climatic change are those that sit between margins of very wet and very dry zones. Their extent is determined by the gradients at the margins. Steep gradients define small areas of high sensitivity, whereas gentle gradients appear as large areas of high sensitivity. Adjustments to the model for differing local surface conditions on different islands can be easily made, which allows a sensitivity assessment of individual islands, even for islands with no climate station data. The approach could be a powerful tool to gain useful information on the influence of climate change on freshwater resources of low islands. Planning decision‐making is possible without knowing precisely the magnitude of climate change that might occur.